Legal Regulation of Surrogacy ın Georgia - Khurtsidze, Ia (European Scientific Journal, ESJ, 2017)
The present article reviews the legislation related to surrogacy in Georgia. It refers to the shortcomings provided in the legal regulations governing these issues and offer the recommendations for their elimination. Besides, the judgment made by the Tbilisi City Court Civil Panel on July 23, 2015 is considered which may be said to be of precedent character.